A comparative study of fine needle aspiration cytology, ultrasonography and radionuclide scan in the management of solitary thyroid nodule : A prospective analysis of fifty cases - Kaur, Kamaljit (Springer India, 2002)
Solitary thyroid nodule is a common clinical entity encountered by the otorhinolaryngologist and physcians. The optimum diagnostic strategy for the euthyroid patient with a soilitary thyroid nodule is still a matter of debate. The goal of diagnostic workup now is to select those patients for surgery who have a high likelihood of harbouring malignancy in the solitary thyroid nodule. The present study was undertaken to evaluate the utility of FANC in the preoperative diagnosis of solitary thyroid nodule and to evaluate the efficacy of FNAC, VSG and RNS in differentiating between benign and malignant nodules. It was found that FNAC is a safe, reliable and cost effective diagnostic modality with a high sensitivity of 83.3% and specificity of 100% and is the single best investigation for preoperative evaluation of solitary thyroid nodules to differentiate between benign and malignant nodules.